2020
DOI: 10.21203/rs.2.20616/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Behavioural plasticity of Anopheles coluzzii and Anopheles arabiensis undermines LLIN community protective effect in a Sudanese-savannah village in Burkina Faso

Abstract: Background: Despite the overall major impact of Long Lasting Insecticide treated Nets (LLINs) in eliciting individual and collective protection to malaria infections, some sub-Saharan Countries, including Burkina Faso, still carry a disproportionately high share of the global malaria burden. This study aims to analyse the possible entomological bases of LLIN limited impact, focusing on a LLIN-protected village in the Plateau Central region of Burkina Faso. Methods: Human Landing Catches (HLCs) were carried out… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…coluzzii evolution across the continent (6, 7). The adaptive flexibility of this mosquito has been also highlighted by its rapid competence to expand its range of peak biting times in order to avoid insecticide treated bed-nets (8). This extraordinary adaptative capacity makes this malaria vector a threat for malaria control.…”
Section: Introductionmentioning
confidence: 99%
“…coluzzii evolution across the continent (6, 7). The adaptive flexibility of this mosquito has been also highlighted by its rapid competence to expand its range of peak biting times in order to avoid insecticide treated bed-nets (8). This extraordinary adaptative capacity makes this malaria vector a threat for malaria control.…”
Section: Introductionmentioning
confidence: 99%
“…Field studies in East Africa have reported increased zoophagy [23,24,28], feeding outdoors or early evening biting [29] and changes in resting behaviour from indoor to outdoor [28,30,31]. These behavioural changes might have been due to selection pressure from increased coverage of LLINs [32][33][34][35]. The scale-up of LLINs in Africa has been associated with a species shift from the highly endophilic An.…”
Section: Introductionmentioning
confidence: 99%